Redescription of the poorly known pea crab, Pinnixa plectrophoros Glassell, 1935 (Decapoda: Pinnotheridae), from the Gulf of California - Salgado-Barragán, Jose; Barragán, Ana K.; Berrian, James E. (Zootaxa, 2018)
A complete redescription of the pinnotherid crab, Pinnixa plectrophoros Glassell, 1935, is presented. Glassell’s original description of P. plectrophoros, although without any accompanying illustrations, includes a series of morphological characteristics that help, to a certain extent, correctly identify the specimens of the species. A detailed examination of the holotype and specimens collected from Bahía Santa María-La Reforma, Sinaloa, in the central Gulf of California, revealed that the species has features, such as spines and tubercles, which were not mentioned in the original description. The original description of Pinnixa plectrophoros by Glassell (1935b) is hereby modified on the basis of the holotype, deposited in the San Diego Natural History Museum (SDNHM) and fresh material from Sinaloa, central Gulf of California, including illustrations and a photograph of color in life. The specimens from Sinaloa correspond to the second record of the species, 870 km southeast of the type locality.